Sistem Informasi Geografis Untuk Penjadwalan Kajian Islam Pada Kota Banjarmasin Dengan Menerapkan Metode Rapid Application Development - Rahman, Muhammad Saidi; Muflih, M.; Wijaya, Yusup Indra; Alamsyah, Nur (LPPM STIKOM Tunas Bangsa, 2024)
The importance of spreading Islamic religious knowledge through studies and lectures has become a primary focus in efforts to enhance the understanding of the community regarding Islamic teachings. According to data from BPS in 2018, there are more than 200 mosques scattered throughout Banjarmasin City. In addition to mosques, Banjarmasin City also has a significant number of majlis ta'lim. These mosques and majlis ta'lim certainly have various schedules for Islamic studies, ranging from daily, weekly, to monthly schedules. Currently, there is no system in Banjarmasin City that provides information about the scheduling of Islamic studies, making it difficult for the community to find information on where to look for these activities. Besides scheduling information, to facilitate the community in finding the location of Islamic studies, geographical information of each mosque and majlis ta'lim needs to be added as well. The system development method uses Rapid Application Development (RAD), resulting in a web-based system using PHP programming language and Leaflet JavaScript plugin for the geographic information system, with MySQL as the database. It is hoped that this system can help the community find information on Islamic study schedules and easily locate the venues for these activities.